Site-Directed Mutagenesis of Klebsiella pneumoniae AxMC-originated palI Gene and Its Effect on Sucrose Isomerase Subcellular Localization - Eliana, Elif
Sucrose isomerase have known to be a key player for isomaltulose production. Isomaltulose is a sucrose derived sugar which has slow released and non-cariogenic properties and therefore can perform as an alternative sugar intake for athletes ensuring a longer constant performance. Previous study revealed that the expression of sucrose isomerase encoding gene (palI) in commercial host tend to generate outer membrane bound protein and make it difficult to be purified and characterized. It might be possible that signal peptide (SP) of palI gene played a role in this matter. This study aimed to see the effect of signal peptide deletion on sucrose isomerase subcellular location. The experimental workflow started with in-silico study to predict signal peptide using SignalP 4.0 and PRED-TAT, design the primer and observe the mutation effect on the protein subcellular localization using PSLPred and Cello2Go web-based program. Then the mutation was carried out using inverse polymerase chain reaction (PCR) at optimum temperature where tail-to-tail primers are performed to insert ATG sequence as a new codon start, delete signal peptide and amplify the whole vector all at once. Next, mutant construct was introduced into Escherichia coli BL21 (DE3). The host cell is then fractionated based on its subcellular compartment. Finally, protein expression was confirmed using SDS-PAGE while protein content for each fraction was affirmed using DNS sugar assay. In-silico study showed that mutant construct remained in the same compartment yet less hydrophobic than the wild type. This finding might boost the protein likelihood to be resided in intracellular compartment. DNS assay on mutant sample indicated that sucrose isomerase from mutant construct had very low activity compared to the wild type sample. Meanwhile, SDS-PAGE poorly depicted sucrose isomerase overexpression for mutant sample. Tracing back to sequencing data led to an answer that mutant construct experienced frameshift mutation. Therefore, the effect of signal peptide deletion on sucrose isomerase subcellular localization is not yet to be concluded due to distinct frameshift mutation.